Lebanon Economic Monitor, Fall 2021 : The Great Denial - World Bank (World Bank, Washington, DC, 2022)
The scale and scope of Lebanon’s deliberate depression are leading to the disintegration of key pillars of Lebanon’s post-civil war political economy. Monetary and financial turmoil along with surging inflation continue to drive crisis conditions. Public finances improved in 2021 as spending collapsed faster than revenue. Lebanon urgently needs to adopt and implement a credible, comprehensive, equitable reform plan if it is to avoid a complete destruction of its social and economic networks and immediately stop irreversible loss of human capital.